HUBUNGAN ANTARA DUKUNGAN SOSIAL KELUARGA DENGAN TINGKAT KECEMASAN PASIEN RAWAT INAP DI RSU PKU MUHAMMADIYAH GOMBONG - Catur Budi Hartono; marsito -; Arnika Dwi Asti (Jurnal Ilmiah Kesehatan Keperawatan, 2009)
Most of us commonly have ever been hospitalized, and hospitalization can create anxiety. Anxiety level is influence bay many factors such as physic, environment, economy, knowledge level, social, and also family social support. It was a correlation research by using Cross Sectional approach. There were 97 respondents as the samples in this research. They were the patients who were hospitalizing in long stay ward PKU Muhammadiyah Gombong Hospital. The samples were taken by Purposive Sampling technique. The research was conducted in 14, 21, and 28 of August 2008. The data were taken by using questionnaire. The research finding show that 58 respondents (55.67%) experience medium anxiety, 8 respondents (8.25%) experience serious anxiety, and the rest have low and very serious anxiety (panic). Mine while 41 respondents (42.27%) got medium family social support, 50 respondents (51.55%) got family social support, and the rest got low family social support. The hypothesis test use was Spearman Rank correlation. The research finding that is not correlation between family social support with long stay patient anxiety level with the value p=0.489 (p > 0.05). From the research writhed concluded that social support given by the family did not totally influence ounce’s anxiety level.   Keywords: social support, family, anxiety level, long stay treatment